1999
DOI: 10.1002/1529-0131(199908)42:8<1628::aid-anr10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental autoimmune arthritis by nasal administration of a type II collagen-cholera toxoid conjugate vaccine

Abstract: Objective. To assess the efficacy of intranasal administration of microgram amounts of type II collagen (CII) coupled to cholera toxin B subunit (CTB) with respect to the development of collagen-induced arthritis, even when given after the onset of clinically evident arthropathy.Methods. DBA/1 mice were immunized with CII to induce arthritis and were subsequently treated with CTB-CII, CTB-conjugated ovalbumin, or CII alone. The incidence and severity of arthritis were assessed clinically and histologically.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 26 publications
4
61
0
Order By: Relevance
“…OVA/CTB treatment to induce functional suppression of T cell responses. It is notable that mucosal Ag/CTB treatment not only increases TGF-␤ production, as shown in this study and in previous reports (19,22), but also almost completely suppresses proinflammatory IL-6 production (21). In light of the recent finding by Bettelli et al (27) that TGF-␤ in the absence of IL-6 strongly promotes T reg generation but when combined with IL-6 instead, induces IL-17-producing, so-called Th17 effector T cells, the combined increase in TGF-␤ and decrease in IL-6 is put forward as an important explanation for the remarkably efficient oral tolerance induction and T reg generation by Ag/CTB treatment.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…OVA/CTB treatment to induce functional suppression of T cell responses. It is notable that mucosal Ag/CTB treatment not only increases TGF-␤ production, as shown in this study and in previous reports (19,22), but also almost completely suppresses proinflammatory IL-6 production (21). In light of the recent finding by Bettelli et al (27) that TGF-␤ in the absence of IL-6 strongly promotes T reg generation but when combined with IL-6 instead, induces IL-17-producing, so-called Th17 effector T cells, the combined increase in TGF-␤ and decrease in IL-6 is put forward as an important explanation for the remarkably efficient oral tolerance induction and T reg generation by Ag/CTB treatment.…”
Section: Discussionmentioning
confidence: 56%
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in addition to functioning as a carrier for the cholera toxin A subunit to target adenylate cyclase, CTB can exert immune-modulating effects independent of the A subunit (30,31). CTB has been reported to suppress the onset of T cell-dependent autoimmune diseases and to potentiate tolerance of the adaptive immune response (32)(33)(34). Pretreatment of macrophages with CTB has been reported to suppress the LPS-induced production of TNF-␣ and IL-6 (30, 31).…”
Section: Mkp-1 Is Induced By the Immune-modulatory Agents Dexamethasomentioning
confidence: 99%
“…At present, T cell recognition of only a limited number of self-Ags has been described in RA, e.g., type II collagen (19,20), human cartilage glycoprotein 39 (HC gp-39) (21), hsp60 (22,23), chondrocyte Ag 65 (24), synovial fluid-derived p205 (25), and the endoplasmatic reticulum molecular chaperone BiP (26). In this study, we have identified several new targets for the immune system during the arthritis process.…”
Section: Discussionmentioning
confidence: 62%